INTEGRASI TRADISI LITERASI KEAGAMAAN (YASINAN) DALAM TERCIPTANYA BUDAYA KERUKUNAN MASYARAKAT - Muhamad Bisri Mustofa; Rahmat Iqbal; Aan Budianto; Nur Hidayat (Fakultas Ilmu Komunikasi Universitas Islam Nusantara, 2022)
Yasinan is an Islamic tradition in the archipelago which is an attempt to introduce Islamic culture (Islam and culture) that is unique to Indonesia. Yasinan is also a religious literacy that increases the knowledge of Muslims about the holy book al-Qur'an by reading it and writing it. Muslims are always reminded of the importance of literacy in various letters including Surah Al-Alaq verses 1-3 and Surah Al-Isra 'verse 14. This tradition is a medium for the welfare of the community and as a means of giving charity. This tradition is also a means of gathering among community members so that all information about the local environment is conveyed by the head of the RT after the yasinan series is carried out. In addition, Yasinan can also be seen as the glue of social relations between residents, when participating in the Yasinan event, residents who did not know each other yesterday will become acquainted. The Yasinan event can strengthen the relationship between fellow residents, especially neighbors and the surrounding community. In addition, the participation of residents in participating in the Yasinan event can foster a sense of empathy and sympathy for the community to share what is felt by the people who hold the Yasinan event. In preparation for serving food, the women and men work together to make dishes that have been financed by the host who has an intention. Therefore, through Yasinan formed a religious literacy that introduces Islamic culture (Islam and culture) that is unique to IndonesiaKeywords: religious literacy, culture of harmony, globalization eraABSTRAKYasinan merupakan sebuah tradisi Islam di Nusantara merupakan usaha memperkenalkan budaya Islam (Islam dan budaya) yang khas ada di Indonesia. Yasinan juga sebagai literasi keagamaan yang meningkatkan pengetahuan ummat muslim mengenai kitab sucinya al-qur’an dengan membacanya dan menulisnya. Ummat Islam selalu diingatkan akan pentingnya sebuah literasi diberbagai surat diantaranya surat al-alaq ayat 1-3 dan surat al-isra’ ayat 14. Tradisi ini menjadi media penyejahtera masyarakat dan sebagai sarana bersedekah. Tradisi ini juga sebagai sarana berkumpul antar anggota masyarakat sehingga seluruh informasi terhadap lingkungan setempat disampaikan oleh ketua RT setelah rangkaian yasinan dilaksanakan. Selain itu, Yasinan juga dapat dipandang sebagai perekat hubungan sosial warga, ketika mengikuti acara Yasinan, maka warga yang kemarin tidak kenal satu sama lain akan menjadi kenal. Acara Yasinan dapat mempererat tali silaturahmi antar sesama warga, terutama tetangga dan masyarakat sekitar. Disamping itu juga dengan keikutsertaan warga mengikuti acara Yasinan dapat menumbuhkan rasa empati dan simpati masyarakat untuk ikut merasakan apa yang dirasakan oleh orang yang mengadakan acara Yasinan. Dalam persiapannya menyajikan makanan, para kaum perempuan dan laki-laki saling gotong-royong untuk membuatkan masakan yang telah dibiayai oleh tuan rumah yang memiliki hajat. Oleh karena itu, melalui Yasinan terbentuk sebuah literasi keagamaan yang memperkenalkan budaya Islam (Islam dan budaya) yang khas ada di Indonesia.